TO EVALUATE AND COMPARE THE EFFECTIVENESS OF ADVANCED PLATELET-RICH FIBRIN (A-PRF) COMBINED WITH 1% METRONIDAZOLE GEL VERSUS A-PRF ALONE IN THE TREATMENT OF CHRONIC PERIODONTITIS OVER A 12-WEEK PERIOD - DR. PRAGYA TRIPATHI; DR. DEEPANSHU PANWAR; DR. PREETI UPADHYAY; DR. SIDDHANTH SINGH; DR. TULLIKA ROY; DR. MANPREET KAUR (The Bioscan, 2025)
Aim To evaluate and compare the effectiveness of advanced platelet-rich fibrin (A-PRF) combined with 1% metronidazole gel versus A-PRF alone in the treatment of chronic periodontitis over a 12-week period. Introduction Periodontitis is a prevalent inflammatory condition characterized by the destruction of periodontal tissues, largely driven by microbial infection. Regenerative therapies such as advanced platelet-rich fibrin (A-PRF) have shown promising outcomes due to their ability to promote healing and tissue regeneration. Metronidazole, a widely used antimicrobial agent, has demonstrated efficacy in targeting anaerobic pathogens involved in periodontitis. This study investigates the potential synergistic effect of combining A-PRF with 1% metronidazole gel to enhance clinical outcomes in patients with chronic periodontitis. Objective To assess and compare the clinical efficacy of A-PRF in combination with 1% metronidazole gel versus A-PRF alone in reducing plaque, gingival inflammation, probing pocket depth, and improving clinical attachment levels in chronic periodontitis patients. Methodology This 12-week randomized clinical trial included 60 periodontal sites from patients aged between 30 to 65 years, randomly allocated into two groups. • Group A: Received A-PRF combined with 1% metronidazole gel • Group B: Received A-PRF alone Clinical parameters including Plaque Index (PI), Gingival Index (GI), Probing Pocket Depth (PPD), and Clinical Attachment Level (CAL) were recorded at baseline, 4 weeks, and 12 weeks. Statistical analysis was conducted to evaluate intra- and intergroup differences. Results Both groups exhibited statistically significant improvements in all clinical parameters over the 12-week period. However, Group A showed significantly greater reductions in PI, PPD, and CAL compared to Group B at 12 weeks (p < 0.001). Although GI improved significantly within both groups, the intergroup difference was not statistically significant. Conclusion The combination of A-PRF and 1% metronidazole gel provides enhanced therapeutic benefits in the management of chronic periodontitis compared to A-PRF alone. This dual-action approach not only reduces the microbial load effectively but also supports tissue regeneration. Further clinical studies with larger sample sizes and extended follow-up periods are recommended to validate and extend these findings.